Complete chloroplast genome of Exacum affine (Gentianaceae): the first plastome of the tribe Exaceae in the family Gentianaceae - Wang, Jiuli (Mitochondrial DNA B Resour, 2019)
Exacum affine Balf.f. ex Regel is a traditional medicinal plant in Yemen and also a popular potted plant. In this study, we sequenced the complete chloroplast genome of E. affine on the Illumina HiSeq Platform. The plastome sequence is 153,311 bp in length with a typical quadripartite structure, containing a pair of inverted repeated (IR) regions of 26,079 bp that are separated by a large single copy (LSC) region of 83,724 bp, and a small single copy (SSC) region of 17,509 bp. The GC content of the whole cp genome was 43.14%. A total of 132 functional genes were annotated, including 87 protein-coding genes, 37 tRNA genes, and 8 rRNA genes. The complete plastome sequence of E. affine will provide genetic and genomic information to promote its horticulture, officinal utilisation and systematics research of Gentianaceae (especially the tribe Exaceae).